Secondary Metabolites from Marine Microorganisms. II. Marine Fungi and Their Habitats - T. I. Orlova; V. G. Bulgakova; A. N. Polin (Антибиотики и Химиотерапия)
Marine-derived fungi are of great interest as a new promising source of biologically active products such as anticancer compounds, antibiotics, inhibitors of biochemical processes. Since marine organisms inhabit biologically competitive environment with unique conditions, the chemical diversity of the secondary metabolites from marine fungi is considerably high. Recent genomic studies demonstrated that fungi can carry gene clasters encoding production of previously unknown secondary metabolites. Activation of the attenuated or silent genes would be useful either for improving activities of the known compounds or for discovery of new products.